INPP5D inhibition attenuates amyloid pathology through the regulation of microglial functions. (20th December 2022) - Lin, Peter Bor‐Chian; Tsai, Andy Po‐Yi; Soni, Disha; Lee‐Goseelin, Audrey; Nho, Kwangsik; Lamb, Bruce T; Oblak, Adrian L
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, robust microgliosis, neuroinflammation, and neuronal loss. Genome‐wide association studies recently highlighted a prominent role for microglia in late‐onset AD (LOAD). Specifically, inositol polyphosphate‐5‐phosphatase ( INPP5D ) is selectively expressed in brain microglia and one of its common intronic variants (rs35349669; OR=1.08, 95%CI=1.06‐1.11) has been reported to be associated with increased risk of LOAD. INPP5D is linked to the triggering receptor expressed on myeloid cells 2 (TREM2) signaling, but little is known about the function of INPP5D in microglia and how INPP5D regulates TREM2‐related AD pathogenesis. Therefore, we aim to understand the role of INPP5D in microglia and AD pathology. Method: We performed differential gene expression analysis to investigate INPP5D expression in LOAD and its association with plaque density using transcriptomic data from the Accelerating Medicines Partnership for Alzheimer's Disease (AMP‐AD) cohort. We also performed quantitative real‐time PCR, immunoblotting, and immunofluorescence assays to assess INPP5D expression and microglial markers in the 5xFAD amyloid mouse model with INPP5D deficiency. Behavioral deficits were assessed by the Y‐maze assay in all animal cohorts at 4‐ and 6‐month of age. The primary microglial culture was used the evaluate the amyloid uptake ability of microglia. Result: INPP5D gene expression was upregulated in LOAD and positively correlated with amyloid plaque density. Inpp5d expression increased as the disease progressed in the 5xFAD mice, and selectively in plaque‐associated microglia. Inpp5d deficiency mitigated the plaque burdens and neuropathology in the 5xFAD mice and further protected against behavioral deficits induced by amyloid pathology. Inpp5d deficiency modulates the microglial signaling, including Trem2 expression and Syk phosphorylation, and further upregulates the expression of the post‐synaptic marker. In the primary microglial culture, Inpp5d inhibition increased the uptake of fibril amyloid beta‐peptide. Conclusion: Our findings show that INPP5D expression increases throughout the AD progression and is predominantly in plaque‐associated microglia. Importantly, INPP5D deficiency reduces Abeta pathology through the regulation of microglial functions, highlighting INPP5D as a potential therapeutic target.